Effects of probiotics on pancreatic inflammation and intestinal integrity in mice with acute pancreatitis - Duangporn Werawatganon; Sarocha Vivatvakin; Kanjana Somanawat; Somying Tumwasorn; Naruemon Klaikeaw; Prasong Siriviriyakul; Maneerat Chayanupatkul (BMC, 2023)
Abstract Background Severe acute pancreatitis is a potentially life-threatening disease. Despite being a common disorder, acute pancreatitis lacks a specific treatment. The present study aimed to examine the effects of probiotics on pancreatic inflammation and intestinal integrity in mice with acute pancreatitis. Methods Male ICR mice were randomly divided into 4 groups (n = 6 per group). The control group received two intraperitoneal (i.p.) injections of normal saline as a vehicle control. The acute pancreatitis (AP) group received two i.p. injections of L-arginine 450 mg/100 g body weight. AP plus probiotics groups received L-arginine to induce acute pancreatitis as above. In the single-strain and mixed-strain groups, mice received 1 mL of Lactobacillus plantarum B7 1 × 108 CFU/mL and 1 mL of Lactobacillus rhamnosus L34 1 × 108 CFU/mL and Lactobacillus paracasei B13 1 × 108 CFU/mL by oral gavage, respectively for 6 days starting 3 days prior to the AP induction. All mice were sacrificed 72 h after L-arginine injection. Pancreatic tissue was obtained for histological evaluation and immunohistochemical studies for myeloperoxidase, whereas ileal tissue was used for immunohistochemical studies for occludin, and claudin-1. Blood samples were collected for amylase analysis. Results Serum amylase levels and pancreatic myeloperoxidase levels in the AP group were significantly higher than in controls and significantly decreased in probiotic groups compared with the AP group. Ileal occludin and claudin-1 levels were significantly lower in the AP group than in controls. Ileal occludin levels significantly increased, whereas ileal claudin-1 levels did not significantly change in both probiotic groups as compared with the AP group. The pancreatic histopathology showed significantly higher degree of inflammation, edema, and fat necrosis in the AP group, and these changes improved in mixed-strained probiotic groups. Conclusions Probiotics, particularly the mixed-strain ones, attenuated AP via the reduction of inflammation and the maintenance of intestinal integrity.